The Influence of Work Motivation and Education Level on Employee Performance at Online Ojek Drivers PT.Application Karya Anak Bangsa/PT.GO-JEK Bandung - Syukran H Abdul; Dede Hertina (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
One of the businesses that is currently developing is a transportation service business by motorbike or what used to be called an online-based motorcycle taxi. Almost every corner of major roads and remote places there are online motorcycle taxi drivers. If you look closely, there are many things that must be addressed in the current ojek service, especially the issue of safety, courtesy and fairness of service prices. Children of the Nation (GO-JEK) Bandung. This type of research is correlation research with quantitative methods. The population of this research is 8413 Go-Jek drivers in Bandung. Sampling of 100 drivers using non-probability sampling method and using purposive sampling. The data analysis technique used multiple linear regression with SPSS version 20. The results showed that based on a partial hypothesis test (t test) and simultaneous (F test) it can be seen that work motivation and education level have a partial and simultaneous effect on employee performance at PT. Karya Anak Nation (GO-JEK).